Development of Animated Videos Based on the Cupcut Application to Improve Mastery of Vocabulary in Maharah Istima' at SDN 7 Banda Aceh - Falah, Moch. Fajarul; salmiyanti; Adzhim, Said Kasyful (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2026)
This study aims to improve the ability of students of SDN 7 Banda Aceh in mastering Arabic vocabulary through Maharah Istima', by developing animated video media based on the Cupcut application. The research method used is R&D (Research and Development) research, with the ADDIE model which has 5 stages which include: Analyze, Design, Development, Implementation and Evaluation. The results of this study are that animated videos can improve students' istima' skills in mastering vocabulary. This can be seen from the ease with which students understand the material. Initially, students were less able to pronounce vocabulary correctly and had difficulty remembering vocabulary, and after the researcher used this media, students easily remembered it. In addition, in applying the media, the researcher provided sufficient opportunities for each student to actively participate in pronouncing vocabulary and listening to the correct sound of vocabulary. So that students experienced significant progress from difficulty in pronouncing vocabulary to being easy to pronounce, and from having difficulty remembering the meaning to being easy to remember. and students became very enthusiastic in learning.